Official tenure and governance effectiveness of China's basic pension insurance system: An inverted U-shaped curve - Li, Zhiguang; Si, Xu; Zhang, Wei; Feng, Zhipei; Li, Tingjing; Guo, Yige (Frontiers in Public Health, 2022)
Objectives: Based on incentive theory of motivation, this paper aims to estimate China’s basic pension insurance’s annual efficiency and explore the relationship between official tenure and governance effectiveness. Methods: The DEA—BCC model was used to evaluate the operating efficiency of basic pension insurance in 31 provinces of China. And four-panel Tobit models were constructed to examine the heterogeneous linkages between officials’ tenure and governance efficiency in different regions of China. Results: The results showed that there was an inverted U-shaped relationship between the official tenure and the governance efficiency of basic pension insurance. The younger an official was in his current position, the more apparent the inverted U-shaped relationship between the tenure of an official and the governance efficiency of basic pension insurance. We also found that localized government officials showed better governance efficiency of basic pension insurance. However, as the term of office of officials increased, the governance efficiency of non-localized officials showed a steeper negative effect.